Factors Associated with Reduced Blood Glucose Levels in Patients with Diabetes Mellitus: The Role of Oral Antidiabetic Therapyand Dietary Patterns - Ahmad Azrul Zuniarto; Siti Pandanwangi TW; Deria Deria (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Diabetes mellitus is a chronic disease that requires proper blood glucose control through appropriate dietary patterns and antidiabetic therapy. Objective: This study aims to analyze the association between dietary patterns and oral antidiabetic therapy with the effectiveness of blood glucose reduction in patients with diabetes mellitus in several health facilities in the Cirebon and Majalengka regions. Methods: This study used an observational cross-sectional design. Data were collected through medical records and the Food Frequency Questionnaire (FFQ). Results and Discussion: The results show that most patients had good dietary patterns, with 53 out of 69 patients (76.8%). In the oral antidiabetic therapy variable, 56 out of 69 patients (81.2%) who used oral antidiabetic drugs showed effective blood glucose reduction. The analysis of dietary patterns indicates that good dietary patterns are associated with a higher likelihood of effective glucose reduction in Cirebon City (OR 0.600; 95% CI: 0.058–6.213), Cirebon Regency (OR 2.500; 95% CI: 0.100–62.605), and Majalengka Regency (OR 0.826; 95% CI: 0.685–0.996). Regarding antidiabetic therapy, the use of Metformin shows a 3.5 times greater likelihood of achieving effective glucose reduction compared to Glibenclamide (OR 3.500; 95% CI: 0.435–28.138). Combination therapy is more favorable in Cirebon Regency (OR 0.100; 95% CI: 0.004–2.504), while in Majalengka Regency, the effectiveness between single and combination therapy is relatively similar (OR 1.167; 95% CI: 0.142–9.586). Conclusion: Overall, this study confirms that good dietary patterns and appropriate oral antidiabetic therapy regimens play an important role in improving the effectiveness of blood glucose control in patients with diabetes mellitus.